BUDDHADHAMMA APPLICATION FOR PEOPLE’S POLITICAL AWAKENING PROMOTION AFFECTING LOCAL ELECTION OF PHANNA NIKHOM SUB-DISTRICT MUNICIPALITY IN SAKON NAKHON PROVINCE - Chaibunta, Chadarat; Sowkasem, Anubhumi; Boonrueang, Sumalee (Journal of MCU Nakhondhat, 2024)
This article aims to study 1) The level of political awareness of people in local elections, 2) Factors affecting political awareness of people in local elections, and 3) Presenting the application of Buddhist principles to promote political awareness of people. People who affect local elections in Phanna Nikhom Subdistrict Municipality Sakon Nakhon Province. The research methodology is a mixed-methods research. Quantitative research using a questionnaire with a reliability value of 0.931. The sample population was 333 people. The data were analyzed using frequency, percentage, mean and standard deviation. Qualitative research using in-depth interviews with 10 key informants. The data are analyzed descriptively. The research results found that 1) The political awareness of the people in the local elections was at a moderate level overall. 2) Factors affecting the political awareness of the people in the local elections found that the factors affecting the political awareness in the local elections were in 3 aspects: political knowledge, political understanding, and political interest. The Threefold Training had a positive relationship with the political awareness of the people at a statistical significance level of 0.01. 3) The application of Buddhist principles to promote the political awareness of the people that affected the local elections in Phanna Nikhom Subdistrict Municipality, Sakon Nakhon Province. Applying the Threefold Training i.e. higher training in morality, concentration, and wisdom to promote political awareness will lead to peace in the community, unity among the people, prioritize the collective good, be reasonable, adhere to the principles of correctness and make appropriate decisions in the election.